Understanding the operational problems and fouling characterization of RO membrane used for brackish water treatment via membrane autopsy - Balçık, Çiğdem (Iwa Publishing, 2021)
An autopsy of spiral wound RO membrane operated in brackish water treatment was conducted to understand the origin and extent of foulants and fouling mechanisms. Structural and chemical characterization was determined by visual inspection and instrumental analysis such as SEM-EDS and XRD. It was observed that the membrane surfaces were completely covered with a gray/brown pollutant layer in all membrane sheets. SEM images proved accumulation of mineral pollutants on membrane surface. Also, the high levels of Al and Si which was attributed to aluminum silicates originating from feed water were determined on membrane surfaces. Additionally, the XRD analysis results showed that the foulant sample collected from membrane surfaces include halloysite, SiO2 and LiCl components. Fujiwara result proved that no damage was occurred on the membrane surface due to oxidation. Consequently, a fouling control strategy for RO-based brackish water treatment plants was also recommended to increase the membrane life.
Keywords: fouling; membrane; membrane autopsy; reverse osmosis